Nonrenewable Resource Scarcity - Krautkraemer, Jeffrey A. (Journal of Economic Literature, 1998)
Nonrenewable resource theory often is summarized by Hotelling's rule. This paper reviews theoretical extensions and empirical investigations of resource extraction models. Observed data are often inconsistent with the Hotelling rule, suggesting that other characteristics of nonrenewable resource supply, including exploration, heterogeneous ore quality, technological progress, and capital investment, are important determinants of the dynamic behavior of resource prices. Given the persistent recurrence of concern about nonrenewable resource scarcity, measures of nonrenewable resource scarcity and the empirical evidence for the time trends of those measures are reviewed. Finally, the implications of nonrenewable resource scarcity for economic growth are examined.